A study of eco-performane of logistics services in food supply chains - Li, Dong; Hanafi, Zurina (Springer, Berlin, Heidelberg, 2012)
Transportation is one of the main contributors of greenhouse gases which give direct negatives impact on environment.Management of logistics services plays an important role in maintaining business competitiveness as well as social responsibility. Optimising logistics service with integrated economic and ecological objectives can help to reduce negative impact on the environment by reducing the amount of carbon emissions and improving operations efficiency. This study focuses on multimodal transportation planning and optimal strategies with a UK food supply chain case under carbon emissions control. The research investigates and identifies impact of the policies on logistics performance.